Strategy of Balancing in Turkish Foreign Policy - D. B. Grafov (Vestnik MGIMO-Universiteta)
The new offensive approach of Turkey's foreign policy is the sign of President Erdogan's ambitions to redistribute power in the Middle East and the Eastern Mediterranean and a way to legitimize his own regime. On the one hand, this can be seen as the ambitions of «neo-Ottomanism», on the other hand, there is a new attempt to solve five foreign policy problems: the «Kurdish issue», the «Aegean dispute», the return of territories mentioned in the “National Oath” (Misak-i Milli), breakthrough from disillusionment with integration with the EU and overcoming inequality in allied relations with the United States to satisfy antiAmerican nationalism.The article examines Turkey's foreign policy since Erdogan gained full control of power and intervened in the civil war in Syria in 2014-2015. The aim is to determine the reason for Turkey's offensive strategy from the perspectives of Neorealism theory of International Relations and Bargaining model of war. The main findings are as follows. Erdogan's policy of power redistribution has focused on relations with the United States, the EU, and Russia as well as regional powers and has employed dominance in bargaining power as the main tool. A show of Turkey's force makes counterparts more compliant and serves as a tool to convince that the cost of deterring Turkey will be greater than the cost of concession.The main feature of Erdogan's policy is the use of contradictions between partners. According to Neorealism, if a state becomes too powerful, the balancing coalition occurs. But Turkey's offensive policy does not face a balancing coalition (or an international system, especially on the NATO and the EU directions), because there are many contradictions between potential opponents, which Erdogan masterfully uses. At some point, Turkey balances each of them by the threat to move closer to its opponent thus creating a balancing lever in “balancing triangle”. In this way Erdogan uses a series of “balancing triangles” to put pressure on Russia, the US, and the EU simultaneously.